Identifikasi Langgam Arsitektur Pada Bangunan Stasiun Radio Malabar Dalam Upaya Pelestarian Cagar Budaya - Salman Algiefar, Muhammad; Maulana Subki, Raksa; Hidayah R, By Nur; Badar Tubanie, Moch. Riou (CV RIFAINSTITUT, 2024)
Identifying architectural styles in cultural heritage buildings involves recognizing the design elements and features that define the building’s identity. These architectural styles often mirror their time's historical, cultural, and technological context, showcasing the diverse influences and local adaptations to global trends. For instance, the architectural style of the Malabar Radio Station can be identified through its design elements, which typically combine European and local styles. During its operational years, Malabar Radio Station played a vital role in facilitating communication and information exchange between Indonesia and the Netherlands. Unfortunately, the station sustained severe damage during the Japanese occupation and the period following Indonesian independence. Identifying the architectural style of cultural heritage buildings is essential for preserving architectural heritage, linking the past with the present, and inspiring future generations to value and protect the existing cultural heritage.